A Challenge of Macro-Meso-Micro Analysis Impacts on Multiracial Nationality Decision Making :Multiracial Thai-Japanese in Bangkok - Thanapum Limsiritong; Tomoyuki Furutani; Karnjira Limsiritong (Inclusive Society and Sustainability Studies, 2021)
Nationality decision making could impact immensely to country structural, society issues, and future population. Exploring the factors and model prediction could dramatical give benefits to Thailand-Japan or as a reference to other countries toward possibility of multiracial nationality decision making, policy approach to future population and international labor management. The case study of Thai-Japanese multiracial nationality decision making could crucial explain to 4 scenarioses under developing and developed country status contexts. The objectives in this exploratory basic factors research are (1) To study the possibility factors of multiracial decision making (2) To adjust the factors impact on multiracial decision making into a model prediction (3) To assess a model in separation of developing and developed country context toward multiracial decision making. This research conduted N=685 of multinaitonality Thai-Japanese in Bangkok (Thailand) under criteria control throught statistic processes requirement, questionnaire survey conducted in purposive sampling via online at Bangkok as the biggest majority province of Japanese migrant in Thailand (Thailand-Japan embassy,2019). PLS-SEM was considered to assess a formative measurement from lower to higher order and mediation model of macro, meso, and micro levels by using SMART-PLS 3.0. The results indicate that Thailand macro level should concern about “Political and governance”, and “Hospital and wellness” factors, Japan macro level should consider to “Economic”, and “Working environment” factors. Also, Thailand meso level have more issue on development factors than Japan, afterward meso factor as an individual background and experience reports that education and passport competency support to multiracial nationality decision making to both Thailand and Japan. As a result, Thailand macro, meso, and micro structure presents to the unrelevance between macro, meso, and micro which causes to unsupport of nationality decision making meanwhile Japan has a potential to escalate a policy toward macro and meso in better positive way with a significant support between macro, meso, and micro structure both direct and indirect to multiracial natonality decision making.